Comparative effectiveness of preventive treatment with dimethyl fumarate-loaded solid lipid nanoparticles and oral dimethyl fumarate in a mouse model of multiple sclerosis - Silva, Gisela Bevilacqua Rolfsen Ferreira da [UNESP]; Neves, Sofia Pereira das; Oliveira, Susana Cristina Roque; Marques, Fernanda; Oliveira, Anselmo Gomes de [UNESP]; Leite, Fábio de Lima; Cerqueira, João José (Elsevier, 2022)
Background: Orally administered dimethyl fumarate (DMF) presents gastrointestinal adverse effects, such as pain and diarrhea, in addition to flushing and lymphopenia. Objective: Solid lipid nanoparticles (SLNs) with DMF were developed for subcutaneous administration. Methods: DMF-incorporated SLNs and free DMF were tested in mice induced with experimental autoimmune encephalomyelitis (EAE). Results: Preventive treatment of free or incorporated DMF were able to reduce the EAE clinical scores, increase the weight of the animals, reduce the lesion area (demyelination and infiltration), reduce microglial fluorescence intensity and reduce the number of microglial cells and astrocytes, when compared to untreated EAE animals. Groups that received DMF had reduced numbers of T cells, B cells and natural killer (NK) cells in the blood, when compared to the non-induced group. Conclusions: DMF incorporated in SLNs was as effective as free DMF in reducing the clinical scores of the animals, but with reduced administrations when given subcutaneously. In addition, SLN-DMF preventive treatment partially prevented a reduction in the percentages of T and B cells, in the blood, when compared to preventive treatment with free DMF (oral), which suggests reduction of lymphopenia.
Keywords: Dimethyl fumarate; Experimental autoimmune encephalomyelitis; Multiple sclerosis; Solid lipid nanoparticles; Subcutaneous route